EXPLORING FACTORS THAT SHAPE INDONESIAN’S INTENTIONS TO PURCHASE HERBAL MEDICINE - Keni Keni; Nicholas Wilson; Purnama Dharmawan (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The pharmaceutical industry has emerged as one of the most rapidly expanding sectors globally, and this trend holds true for Indonesia as well. Within this industry, a notably popular type of medication in Indonesia is herbal medicine. This variant of medicine is derived from traditional and natural ingredients, with minimal incorporation of chemical substances. To delve into this phenomenon, the present study aims to identify the factors influencing Indonesians' inclination and intention to purchase herbal medicine. To achieve this, the study integrates key variables from the original Theory of Reasoned Action (TRA) framework, namely attitude and subjective norm, along with an additional element – perceived value. The methodology employed involves a survey-based approach, utilizing questionnaires as the primary data collection tool among the chosen participants. The sampling method chosen is non-probability purposive sampling, ensuring that only individuals who meet the predetermined criteria participate – specifically, individuals who have acquired herbal medicines within the past 6 months. Employing a 7-point Likert scale, a total of 156 data points were amassed. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), with SmartPLS 4 software being the designated tool. Through the scrutiny of the data, the authors conclude that attitude, subjective norm, and perceived value significantly impact consumers' intention to purchase herbal medicine in Indonesia.